2020
DOI: 10.1037/xlm0000938
|View full text |Cite
|
Sign up to set email alerts
|

From association to gist.

Abstract: We removed a key uncertainty in the Deese/Roediger/McDermott (DRM) illusion. The mean backward associative strength (MBAS) of DRM lists is the best-known predictor of this illusion, but it is confounded with semantic relations between lists and critical distractors. Thus, it is unclear whether associative relations, semantic relations, or both foment the illusion. In Experiment 1, we developed a tool for investigating this question—a normed pool of materials in which subjects rated the gist strength of 120 DRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 71 publications
(159 reference statements)
0
30
1
Order By: Relevance
“…In addition to our approach to separate the effects of associative and thematic similarity by holding BAS constant, other work has addressed the core question of how to tease apart semantic and associative similarity. Specifically, Brainerd et al (2020) created a pool of 120 four-item DRM lists that varied widely in their mean BAS values and in their degree of semantic similarity between list items and CIs. All lists were normed to determine a measure of gist strength (GS) and empirically examine how BAS and GS jointly influence false recognition.…”
Section: Decomposing Semantic and Associative Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to our approach to separate the effects of associative and thematic similarity by holding BAS constant, other work has addressed the core question of how to tease apart semantic and associative similarity. Specifically, Brainerd et al (2020) created a pool of 120 four-item DRM lists that varied widely in their mean BAS values and in their degree of semantic similarity between list items and CIs. All lists were normed to determine a measure of gist strength (GS) and empirically examine how BAS and GS jointly influence false recognition.…”
Section: Decomposing Semantic and Associative Similaritymentioning
confidence: 99%
“…Thus, the benefit from shared features fits nicely with this theory. In addition, the evidence from Brainerd et al (2020), that GS predicts false recognition whereas BAS only does so when GS is low, makes FTT a viable explanatory mechanism for these effects because GS is assumed to influence gist extraction and gist-sensitive retrieval processes. However, the fact that C + A CIs were harder to identify could be problematic, given that a stronger gist should be easier to identify.…”
Section: Decomposing Semantic and Associative Similaritymentioning
confidence: 99%
“…In a subsequent memory task, participants often claim to recall or recognize the critical lure (false memories) along with the studied items (true memories) ( Roediger and McDermott, 1995 ). Numerous experimental manipulations have revealed that falsely remembered critical lures present highly compelling memorial evidence of the occurrence of the event (e.g., Beato et al, 2013 ; Boldini et al, 2013 ; Thakral et al, 2019 ; Brainerd et al, 2020 ; Howe and Akhtar, 2020 ; H. Liu et al, 2020 ; Beato and Arndt, 2021 ; Huff et al, 2021 ; Z. Liu et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 The backward associative strength or BAS has been identified as a reliable predictor of false memory and is one of the most commonly cited factors that facilitates error-inflating processes, as research has shown that false recall and false recognition rates were higher in high-BAS than in low-BAS lists (e.g., McEvoy et al, 1999 ; Roediger et al, 2001b ; Gallo and Roediger, 2003 ; Arndt and Gould, 2006 ; Beato and Arndt, 2017 ). However, some studies have also reported that BAS did not affect false recognition rates (e.g., Cadavid et al, 2012 ; Brainerd et al, 2020 ). Although these results are of interest, the aim of the present study is not to shed light on the role of BAS in false memory, as the extremely low-BAS levels employed here are only used as a proxy for low-identifiability levels.…”
mentioning
confidence: 98%
“…Such problems with regard to orthographic representations (reading latencies, writing the words, choice between homophones of the same stimulus) have been described by Martínez-García et al ( 2019 ). A number of studies suggest that superior cognitive abilities such as language are linked with compulsive behavior (Brainerd et al, 2020 ; Piette et al, 2020 ; Ramey et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%